Migration and networks: Does education matter more than gender? - Michel Beine; Sara Salomone (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper looks at the impact of networks on international migration flows to OECD countries. In particular, we look at whether diaspora effects are different across education levels and gender. Using new data allowing to include both dimensions, we are able to analyze the respective impact of networks on the proportion of each category of migrant. Therefore, unlike the preceding literature on macro determinants of international migration, we can identify the respective factors influencing the selection in terms skills and in term of gender. We found that network effects vary by education level but not by gender. Women are also found to be less directly dependent on migration costs unrelated to networks such as distance.
Keywords: F22; O15; 330; migration; human capital; network/diaspora externalities; gender; Internationale Wanderung; Soziales Netzwerk; Geschlecht; Network Externalities; Qualifikation; Bildungsniveau; Frauen; Einwanderung; OECD-Staaten